EFL Lecturers’ Perception and Practice of Screencast Feedback - Nanang Zubaidi (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2021)
he current study aims to deepen knowledge on Indonesian English as a foreign language (EFL) lecturers' perception of screencast feedback, their feedback practice, and the consistency between their feedback practice and perception. To investigate the phenomena, five Indonesian university-level EFL lecturers and their EFL students (N=30) were recruited to participate in the study. The researcher employed several data collection techniques including open ended pre-survey, students' essay collection, think-aloud protocol, and semi-structured interviews. The results showed that the EFL teacher participants have positive perception and towards screencast feedback in L2 writing, which influenced their feedback practice. However, the study also discovered two inconsistencies between the teachers' perception of the focus and the type of feedback they provided and their actual practice.